Efficiency of Rearing the African Palm Weevil (Rhynchophorus phoenicis) in Different Substrates as Arsenal for Addressing Malnutrition in Children - Edhebe, Precious O.; Ojianwuna, Chioma C.; Enwemiwe, Victor N.; Esiwo, Eric; Aghahowa, Ehimwenma; Ifeta, Sarah; Oborayiruvbe, Treasure E. (International Journal of Child Health and Nutrition, 2025)
Background: Rhynchophorus phoenicis is arguably one of the most sought-after edible insects in the tropics. It is widely distributed in Africa and is a major pest of palm trees in Africa, Southern Asia, and South America. Globally, the population has been predicted to surpass 9 billion by 2050, leading to food insecurity. Objective: This research investigated rearing the edible insect (Rhynchophorus phoenicis) in different substrates under laboratory conditions to address problems associated with the weevils' availability for solving malnutrition issues in children when consumed. Methods: Ten (10) adult palm weevils were reared in different substrates (coconut husk, sugarcane, pawpaw, and a combination of all the substrates) under laboratory conditions with palm fiber as the control and arranged in triplicates to assess their emergence and survival. Data on larvae emergence, survival, and pupation were obtained within four (4) to eight (8) weeks post-emergence. Results: The rearing experiments showed that larvae emergence and survival (184.08±19.7), pupation rate (53.25±7.0), and adult emergence (12.92±1.8) were highest in coconut husk and least in pawpaw substrate. There was also a significant difference between the larvae emergence and survival, pupation, and adult emergence in the various substrates compared to the control (p<0.05). Implication: The study demonstrated the feasibility of mass-rearing African palm weevil (Rhynchophorus phoenicis) larvae, which, if incorporated into children's diets, will be immensely significant in solving nutritional deficiencies and problems associated with malnutrition.